Foraminifera of the Toarcian-Aalenian boundary from the Lusitanian Basin (Portugal): a paleoecological analysis - Figueiredo, Vera; Canales, M. Luisa; Henriques, M. Helena (Journal of Iberian Geology, 2014)
The detailed study of 37 well preserved benthic foraminiferal assemblages sampled throughout the upper Toarcian-middle Aalenian in two well calibrated sections representing different facies within the Lusitanian Basin (Portugal) - the Maria Pares and the Zambujal de Alcaria sections - has been carried out, aiming at interpreting past environmental conditions. Several mathematical indexes related to diversity, which allows establishing the particular conditions to which the assemblages were submitted, were applied. All the studied assemblages are characteristic of the Jurassic carbonate platforms of the Boreal Realm, in which the Lenticulina genus usually dominates. The Lagenina Suborder is the most abundant, but taking the second more abundant suborder into account, the comparison between coeval sections in the Lusitanian Basin allows the recognition of a regional gradient ranging from the distal part of the platform (Murtinheira) towards the transitional and proximal parts of the shelf (Maria Pares and Zambujal de Alcaria sections respectively). The relative abundances values, as well as the obtained data from the diversity indexes indicate that the studied assemblages are relatively abundant and diverse, reflecting general appropriate paleoenvironmental conditions for their development. Detailed analysis of the data allows the identification in both sections of three different episodes, traducing particular environmental conditions: unstable (Mactra Subzone-lower part of the Opalinum Subzone), favorable and stable (lower part of the Opalinum Subzone-upper part of the Comptum Subzone), and unfavorable (upper part of the Comptum Subzone-lower Bradfordensis Subzone). These data are consistent with previous results obtained in the Murtinheira and São Gião sections, located in the Northern Lusitanian Basin and corresponding to the distal and transitional parts of the platform respectively, and they aimed at contributing to a better understanding of the paleoecological conditions prevailing within the Lusitanian Basin during the Early-Middle Jurassic times.